Odpowiedzi

Najlepsza Odpowiedź!
2010-01-31T20:25:40+01:00
A) x(3x - 2) - 18x² = 5x(2 - 3x) + 6
3x²-2x-18x²=10x-15x²+6
3x²-18x²+15x²-2x-10x-6=0
-12x-6=0
-12x=6
x=-½

b) x² - 2x(x - 1)/3 = x(x/3 +1) - 2
x²-(2x²-2)/3=x²/3 + x - 2 /*3
Obie strony mnożę przez 3, aby pozbyć się postaci ułamkowej
3x²-2x²+2=x²+3x-6
3x²-2x²-x²-3x=-6-2
-3x=-8
x=8/3
x=2⅔

c) x(x -2)/3 - x² - x/2 = x - 3/4 -x(x/6 + 1)
(x²-2x)/3 - x² - x/2= x - 3/4 - x²/6 -x /*12
4(x²-2x) - 12x²-6x = 12x-9-2x²-12x
4x²-8x-12x²-6x=12x-9-2x²-12x
4x²-12x²+2x²-14x+9=0
-6x²-14x+9=0
Δ=b²-4ac=196+216=412
√Δ=2√103
x₁=(6+2√103)/(-12)=-(3+√103)/6
x₂=(6-2√103)/(-12)=-((3+√103)/6


d) x(x - 1)/4 = ½x² + 2/2 /*4
x(x-1)=2x²+4
x²-x-2x²-4=0
-x²-x-4=0
Δ=1-16=-15 <0 nie ma rozwiazania